Spatiotemporal characteristics and determinants of urban expansion in China: perspective of urban agglomerations - Li, Ming; Cao, Yongwang; Song, Jianxin; Li, Huining; Liang, Mengyin (Frontiers in Earth Science, 2025)
IntroductionUrban agglomerations (UAs) are core economic growth centres, and urban construction land is the main spatial carrier of economic growth. Urban expansion is a research hotspot, while previous studies have rarely compared the characters and determinants of urban expansion within and outside UAs.MethodsConsidering the case of China, based on the China Land Use/Cover Dataset (CLUD), this study use spatial statistics analysis and Theil index to compare the spatiotemporal characteristics of urban expansion within and outside UAs during 1990–2020. Economic models is used to detect difference of influencing factors of urban expansion within and outside UAs.ResultsAs for spatiotemporal characteristics, urban expansion is mainly distributed within UAs, especially in UAs at high and upper-middle development levels. In 1991–2020, urban expansion within the UAs accounted for 77.58% of the total urban expansion, and urban expansion in UAs at high and upper-middle development levels accounted for 71.58% of urban expansion in UAs. The inequality of urban expansion between within and outside UAs decreases with fluctuation. The rate of urban expansion outside UAs gradually exceeded that within the UAs from 2011. As for driving factors, government factors have a stronger power to urban expansion than economic factors. Economic factors were more influential within UAs than outside agglomerations. Meanwhile, government forces played more important roles outside urban agglomerations than within agglomerations. The impact of economic factors increased with an upgrade of UA development level, whereas government factors’ impact on urban expansion decreased with upgrade of UA development level.DiscussionThe findings provide a scientific support for urban construction land management. The impact of territorial and spatial planning on urban expansion will be studied.